2020
DOI: 10.3389/fimmu.2020.00708
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Lung Innate Immune Responses Potentially Associated With the Pathogenesis of Acinetobacter baumannii Acute Lethal Pneumonia

Abstract: Acinetobacter baumannii is one of the dominating causes of nosocomial pneumonia, however, very little is known about the host immune response associated with pathogenesis of A. baumannii infection. Here, we used a hypervirulent A. baumannii to establish an acute lethal pneumonia, supported by high bacterial burdens, severe inflammatory cells infiltration and lung damage. The lung transcriptome changes in response to A. baumannii lethal pneumonia were detected by RNA sequencing. The results showed that 6,288 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…They showed that genes related to TNF, cytokine-cytokine receptor interaction, TLRs, NOD-like receptor, NF-κB, Jak-STAT, HIF-1 signaling pathways, apoptosis, and phagosome were significantly upregulated whereas those associated with PI3K-AKT signaling pathway, glycolysis/gluconeogenesis, amino acid, and fatty acid metabolism were downregulated. The study also confirmed the importance of neutrophil-mediated inflammatory responses of innate immune cells in host innate defense against this pathogen (Zeng et al, 2020 ). However, further analysis of the kinetics of these changes will be needed to better define their contribution to the innate immunity against A. baumannii infection.…”
Section: Host Innate Immune Responses To a Baumanniisupporting
confidence: 79%
See 1 more Smart Citation
“…They showed that genes related to TNF, cytokine-cytokine receptor interaction, TLRs, NOD-like receptor, NF-κB, Jak-STAT, HIF-1 signaling pathways, apoptosis, and phagosome were significantly upregulated whereas those associated with PI3K-AKT signaling pathway, glycolysis/gluconeogenesis, amino acid, and fatty acid metabolism were downregulated. The study also confirmed the importance of neutrophil-mediated inflammatory responses of innate immune cells in host innate defense against this pathogen (Zeng et al, 2020 ). However, further analysis of the kinetics of these changes will be needed to better define their contribution to the innate immunity against A. baumannii infection.…”
Section: Host Innate Immune Responses To a Baumanniisupporting
confidence: 79%
“…Their role in the pathogenesis and immunity against A. baumannii appears to be complex due to the multiple functions of most of the cytokines and chemokines. Indeed, Zeng et al ( 2020 ) recently analyzed the lung transcriptome changes in response to lethal intranasal infection with A. baumannii . They showed that genes related to TNF, cytokine-cytokine receptor interaction, TLRs, NOD-like receptor, NF-κB, Jak-STAT, HIF-1 signaling pathways, apoptosis, and phagosome were significantly upregulated whereas those associated with PI3K-AKT signaling pathway, glycolysis/gluconeogenesis, amino acid, and fatty acid metabolism were downregulated.…”
Section: Host Innate Immune Responses To a Baumanniimentioning
confidence: 99%
“…Macrophages are primary effector cells of the innate immune system that form the first line of defense against microbial pathogens [ 42 ]. In this study, we found that Giardia and its secreted PPIB were able to induce macrophage pyroptosis and promote the release of the proinflammatory cytokines IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high survival of Ccl28 -/- mice infected with A. baumannii indicates that CCL28 can play a detrimental role for the host during pulmonary infection. While functioning neutrophils have been described to play a role in controlling Acinetobacter infection (García-Patiño et al, 2017; Grguric-Smith et al, 2015; Van Faassen et al, 2007), an exaggeration of neutrophil recruitment to the Acinetobacter -infected lung is deleterious (Yamada et al, 2013; Zeng et al, 2019, 2020). For example, in one relevant Acinetobacter pneumonia study, depletion of alveolar macrophages increased neutrophil infiltration, promoted extensive tissue damage, and increased systemic dissemination of Acinetobacter (Lee et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%